Evaluation and modelling of biogas production from batch anaerobic digestion of corn stover with oxalic acid - Shitophyta Lukhi Mulia; Arnita Arnita; Wulansari Hilda Dyah Ana (Research in Agricultural Engineering, 2023)
Corn stover is one of the potential lignocellulosic biomasses as the raw material of biogas production. Pretreatment of lignocellulose substrates can enhance biodegradability and biogas yield. This study investigates the effect of oxalic acid pretreatment on biogas production during batch anaerobic digestion of corn stover. First-order, logistic, modified Gompertz and transference models predicted kinetic parameters during biogas production from pretreated corn stover. Results showed that oxalic acid pretreatment significantly affected biogas production (P < 0.05). The highest cumulative biogas yields of pretreated and untreated corn stover were 95.14 mL/gVS and 57.55 mL/gVS, respectively. Pretreated substrates improved biodegradability by 165%. Four kinetic models provided the determination coefficients R2 higher than 0.9. The logistic model and modified Gompertz provided the best deviation of 1.57 and 3.75%, respectively. The logistic model proved the best fitting in predicting cumulative yields and simulating the kinetic model of anaerobic digestion of pretreated corn stover among the three models.